Evaluation of Bactericidal Activity of Electrochemical GO Modified with TiO2 Nanoparticles - Geraldine Durango Giraldo*; Juan Camilo Zapata-Hernández; Claudia Betancur Henao; Juan Felipe Santa Marín; Robison Buitrago Sierra (TecnoLógicas, 2023)
Recently, antibacterial materials have sparked a renewed interest in the fields of biomedical engineering and life sciences. The main purpose of this study was to evaluate the physicochemical properties of TiO2 nanoparticles with anatase phase and an average size of 24.1 ± 4.6 nm, graphene oxide (GO) obtained from the electrochemical method, and TiO2/GO hybrid nanomaterial. Thermogravimetric analysis (TGA) revealed the presence of oxygen functionalities in the GO structure and 23.2 % of TiO2 in the hybrid nanomaterial, as well as a strong interaction between the materials that can be observed in the micrograph of scanning electron microscopy (SEM). Antibacterial tests were performed using the macrodilution method. The results showed that, while GO did not decrease bacterial growth, TiO2 presented high bactericidal activity. In turn, the hybrid TiO2/GO nanomaterial did not show such activity. This result can be explained by the decrease in contact between TiO2 and bacterial cells due to the blocking of the active sites on the TiO2 surface by graphene oxide sheets. These results contribute to the ongoing discussion about the bactericidal properties of graphene oxide.